KELEMBAGAAN DAN TATA HUBUNGAN KERJA PENGELOLAAN BARANG MILIK DAERAH - Zulpikar Zulpikar (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2010)
So far, local governments have not managed their region-owned assets effectively and efficiently so that that they have not proportionally contributed to local revenue and local public services. This condition is mainly due to structural hindrances in theforms of: the indistinctness of job descriptions and functions, the lack of lucid managerial mechanism and standard operating procedures, and inadequacy of resources (human resource, facilities, and finance). The writer recommends that local government should endorse the structure of institution in charge of managing regionowned assets with translucent job descriptions and functions, clear and integrated authority transfer, comprehensible managerial mechanism and standard operating procedures, and sufficient resources comprising human resource, facilities, and financial resource.